2021
DOI: 10.3390/pharmaceutics13020189
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Particle Modelling of Dry Powder Inhalers: Methodologies, Recent Development and Emerging Applications

Abstract: Dry powder inhaler (DPI) is a device used to deliver a drug in dry powder form to the lungs. A wide range of DPI products is currently available, with the choice of DPI device largely depending on the dose, dosing frequency and powder properties of formulations. Computational fluid dynamics (CFD), together with various particle motion modelling tools, such as discrete particle methods (DPM) and discrete element methods (DEM), have been increasingly used to optimise DPI design by revealing the details of flow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Our particles were within the said range [26]. Various studies have identified that particles of sizes between 1-5 µm have the ideal deposition pattern in the airways [27]. However, particles with sizes on either side of the proposed range have a cohesiveness that is not perfect for aerosolization [28].…”
Section: Evaluation Of Ivacaftor and Ciprofloxacin-loaded Microparticlesmentioning
confidence: 66%
“…Our particles were within the said range [26]. Various studies have identified that particles of sizes between 1-5 µm have the ideal deposition pattern in the airways [27]. However, particles with sizes on either side of the proposed range have a cohesiveness that is not perfect for aerosolization [28].…”
Section: Evaluation Of Ivacaftor and Ciprofloxacin-loaded Microparticlesmentioning
confidence: 66%
“…CFD modeling for various DPI devices (Aerolizer ® , Turbuhaler ® , Twincer ® , Handihaler ® , Accuhaler ® , Multihaler ® , etc.) has already been described [54], but to the best of our knowledge the CFD-DPM model of RS01 ® inhaler has not been published in the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, some correlation between in vitro and in silico CFD results has been detected [48][49][50][51][52][53], but there is a need for additional comparative assessment of CFD tools in relation to the in vitro methods to evaluate the applicability of CFD in the research and development of various DPI formulations. A recent review study of Zheng et al (2021) also concluded that more direct comparison between the simulated and experimental results is necessary to improve the prediction accuracy of in silico tools [54].…”
Section: Introductionmentioning
confidence: 99%
“…In order to be successfully delivered and deposited in the lungs, the particles should have an aerodynamic diameter of 0.5 µm to 5 µm, while those with an aerodynamic diameter of less than 3 µm have the chance of reaching the respiratory zone [2]. The particles of such a small diameter generated by the inhaler are very cohesive and can either form drug-only agglomerates or can be attached to larger carrier particles [3,4]. In order for the particles to be effectively transported and deposited in the lungs, processes of particle dispersion and deaggregation are required.…”
Section: Introductionmentioning
confidence: 99%